Electrical Analysis of Fermented Durian Rinds - Siti Rahmah; A Masrukhan Nur; Andreta B Hutahuruk; Kurnia Rizki Siregar; Nelsy Theresia Siggalingging; Rini Selly (Universitas Negeri Medan, 2023)
In this study, Durian rind wastes were fermented using Saccharomyces cerevisiae yeast to break the starch to be smaller sugar molecule. Then, the pH was analyzed using digital pH-meter. The voltage and electric current were analyzed using multimeter. The result showed that the lower the pH value the greater its voltage and its electric current. The pH value influenced by fermentation time. The longer the fermentation time the lower the pH value. The type of microorganism and the composition of durian rind wastes were also affected the pH value. In this study, the fermentation process was set for 24, 48, 72 hours, and the pH value was resulted in the basic range. The highest voltage is 0.094 volt and the highest electric current is 0.058 mA measured in pH 12.3.